Unraveling the structural and compositional peculiarities in CTAB-templated CeO2-ZrO2-MnOx catalysts for soot and CO oxidation - Grabchenko, Maria V.; Mikheeva, Natalia N.; Mamontov, Grigory V.; Corberán, Vicente Cortés; Litvintseva, Kseniya A.; Svetlichnyi, Valerii A.; Vodyankina, Olga V.; Salaev, Mikhail A. (Nanomaterials)
Structure-performance relationships in functional catalysts allow for controlling their performance in a wide range of reaction conditions. Here, the structural and compositional peculiarities in CTAB-templated CeO2-ZrO2-MnOx catalysts prepared by co-precipitation of precursors and their catalytic behavior in CO oxidation and soot combustion are discussed. A complex of physical-chemical methods (low-temperature N2 sorption, XRD, TPR-H2, Raman, HR TEM, XPS) is used to elucidate the features of the formation of interphase boundaries, joint phases, and defects in multicomponent oxide systems. The addition of Mn and/or Zr dopant to ceria is shown to improve its performance in both reactions. Binary Ce-Mn catalysts demonstrate enhanced performance closely followed by the ternary oxide catalysts, which is due the formation of several types of active sites, namely, highly dispersed MnOx species, oxide-oxide interfaces, and oxygen vacancies that can act individually and/or synergistically.